Upaya Peningkatan Pemahaman Preventif Penyakit Malaria dan Diabetes Melitus pada Masyarakat di Manokwari - Dwiranti, Febriza; Sinuraya, Sabarita; Matualage, Dariani (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2019)
Majority of patients comes to the community health centers in Manokwari areas is related to malaria diseases, and small number of patients are for diabete melitus diaseses. The patients of diabetes meliatus coming to these community center are not in prediabetic conditions. This means that they are recommended to look better or advanced treatment in hospital. This conditions are due to community lack of knowledge of malaria and diabetes mellitus (DM). To eliminate these condition, community education is important to be conducted, using different approached such as comunity service. The main targets of this research project are the community living at the rural (sub urban) and town areas. Interviews, biomedical measurement parameter, community approaches, and cutting malaria mosquito living cycle, were used to collect data and information. The results indicate that numbers of family member diagnosed with DM and Impaired Glucose Tolerance (IGT) at Town are higher than those at Rural. The respondents diagnosed DM are mostly women, either as house wife or no regular work. Interestingly, no men were reported for DM. Respondents of DM and IGT from Town were mostly at age of 45 – 54 years old, while at Rural were younger, from 15-24 years old. Malaria were found higher prevalence at the sub urban areas, and mostly suffering from Plamodium falcifarum (tropica malaria). After being community approaches, planting anti-malaria herbs, the prevelance of DM and malaria were decreasing because the community awareness of preventing malaria and DM.